Frequency of Lumbar Spinal Stenosis in symptomatic patients of age â¥ 50 years diagnosed on Magnetic Resonance Imaging (MRI) - Zarak, Muhammad Samsoor; kakar, Kaleemullah; Khan, Alamzeb; Tareen, Bisma; Khan, Rozi; Ullah, Asad (Journal of Medical Biomedical and Applied Sciences, 2018)
Introduction: Lower Back pain with radiation to the lower extremities is a frequent complaint, especially in elderlypeople, and lumbar spinal stenosis (LSS) is one of the underlying conditions. Computed Tomography (CT) orMagnetic Resonance Imaging(MRI) can verify a stenosis in the lumbar spinal region. The incidence and prevalenceof symptomatic lumbar stenosis are rather speculative with no pertinent data. This study is designed to know the bestestimate of LSS in symptomatic patients to help in resource allocation and to make strategies to cut down the morbidity.Subject and Methods: A cross sectional study was done at Neurology and Medicine Department, Bolan MedicalCollege, Quetta. Total duration was from 01/01/2018 to 30/06/2018. A total of 169 symptomatic patients were includedin this study. A detailed history was taken for the duration of symptoms, and MRI was advised. Patients fulfilling thecriteria of lumbar spinal stenosis on MRI reported by the consultant radiologist and having symptoms for more than 3months, were marked as having lumbar spinal stenosis.Results: - The average age of the patients was 63.01 8.39 years Out of 169 cases, 102(60.03%) were male and67(39.64%) female. Frequency of spinal stenosis diagnosed on imaging in symptomatic patients was observed in37.27% (63/169) cases.Conclusion: The results of this study provide significant statistics for doctors that can help in promoting awarenessabout spinal stenosis. In future it might also help to reduce its incidence by designing local protocols and strategiesfor overcoming a problem of such a magnitude which may ultimately help in locating proper funds and proper timeallocation to deal with this disease entity.